A Study On Chip Formation Using Minimum Quantity Lubrication (MQL) Technique - Nasri, Ahmad Raziq An-Nasr; Mohid, Zazuli (Research Progress in Mechanical and Manufacturing Engineering, 2022)
First abstract sentence introduces the research background information and the problem statement. The second sentence explains the main research objectives and their scopes of study. The third sentence describes the methodology, and standard procedures used to conduct the study. The fourth sentence presents key findings and trends that can be observed from the data. The fifth sentence summarizes the discussion regarding those findings and some suggestions for future work.